Aporias : dying--awaiting (one another at) the "limits of truth" (mourir--s'attendre aux "limites de la vérité") - Derrida, Jacques (Meridian (Stanford, Calif.), 1993)
That is the question asked, explored, and analyzed in Jacques Derrida's new book. "Is my death possible?" How is this question to be understood? How and by whom can it be asked, can it be quoted, can it be an appropriate question, and can it be asked in the appropriate moment, the moment of "my death"? One of the aporetic experiences touched upon in this seminal essay is the impossible, yet unavoidable experience that "my death" can never subject to an experience that would be properly mine, that I can have, and account for, yet that there is, at the same time, nothing closer to me and more properly mine than "my death."